Islamic Religious Education Curriculum: Concepts, Implementation, and Challenges in the Modern Era - Edi Saputra; Mujab; Nurul Mubin (LP3M KH Yazid Karimullah Institute, 2026)
The Islamic Religious Education (PAI) curriculum plays a strategic role in shaping students' religious character. This study aims to examine the concept, implementation, and challenges of the PAI curriculum in the modern era. The method used was a qualitative literature study approach. The results of the study indicate that the PAI curriculum is not only oriented towards cognitive aspects, but also affective and psychomotor aspects. The implementation of the PAI curriculum faces various challenges, such as technological developments, social change, and the low integration of values ​​in learning. Therefore, adaptive and contextual curriculum innovation is needed to meet the needs of the times.